2021
DOI: 10.1093/eurjpc/zwab061.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omega-3 polyunsaturated fatty acids in prevention of postoperative atrial fibrillation development in patients undergoing coronary artery bypass graft surgery

Abstract: Funding Acknowledgements Type of funding sources: None. Purpose. To estimate the effect of omega-3 polyunsaturated fatty acids (PUFAs) in prevention of postoperative atrial fibrillation (POAF) in patients with coronary artery disease undergoing coronary artery bypass graft (CABG) surgery. Methods. Studied were 306 patients who underwent CABG. All the patients were divided into two groups depending on the prescription of omega-3 PUFAs in the pre- and postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…Наши результаты согласуются с предшествующими сведениями с литературными источниками [22]. Важное отличие нашего систематического обзоравключение отечественных научных работ [18][19][20][21]. С другой стороны, отечественные публикации по изучению влияния омега-3 ПНЖК на предотвращение ПОФП показали высокий риск систематических ошибок, что послужило причиной невключения данных источников в метаанализ.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Наши результаты согласуются с предшествующими сведениями с литературными источниками [22]. Важное отличие нашего систематического обзоравключение отечественных научных работ [18][19][20][21]. С другой стороны, отечественные публикации по изучению влияния омега-3 ПНЖК на предотвращение ПОФП показали высокий риск систематических ошибок, что послужило причиной невключения данных источников в метаанализ.…”
Section: Discussionunclassified
“…Отечественные публикации также демонстрируют положительное воздействие омега-3 ПНЖК в снижении риска ПОФП, что по результатам работы приводит к уменьшению выраженности гемодинамических нарушений и продолжительности пребывания пациентов в стационаре [18][19][20][21]. Кроме того, исследование Рубаненко О. А. и др.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…PUFAs have been demonstrated to reduce cardiovascular morbidity in animal models [ 105 ]. In a study by Rubanenko O and Rubanenko A [ 106 ], patients treated with PUFAs not only displayed reduced in inflammation and oxidative stress after CABG, but also exhibited a reduction in POAF after CABG. A meta-analysis [ 107 ] of 19 randomised controlled trials (RCTs) conducted in 2017 and a meta-analysis [ 108 ] in 2018 that included 14 RCTs also showed that CABG patients treated with PUFAs displayed a significant reduction of POAF compared to controls.…”
Section: Discussionmentioning
confidence: 99%